Tandem Thioetherification Reactions of 2-(2,2-Dibromovinyl)phenol Derivatives with Thiophenols and Thiols - Geng, Haobing; Du, Juan; Chen, Shanshan; Huang, Qinghua; Zhang, Xiuli; Wang, Lei (Synthesis, 2014)
A tandem thioetherification reaction of 2-(2,2-dibromovinyl)phenol derivatives with thiophenols and thiols has been developed. In the presence of potassium hydroxide, 2-(2,2-dibromovinyl)phenols reacted with thiophenols and thiols to generate 2-arylthiobenzofurans and 2-alkylthiobenzofurans in good yields in N,N-dimethylformamide via a one-pot tandem reaction. This method has several advantages including commercial availability of starting materials, simple operation, and easy purification of products.
Keywords: 2-arylthiobenzofurans; 2-alkylthiobenzofurans; 2-(2,2-dibromovinyl)phenols; tandem reactions; thiols; thiophenols